SYNERGISTIC EXTRACTION OF COBALT(II) WITH MIXTURE OF ACYL-PYRAZOLON AND CROWN-ETHER IN STRONSIUM(II) ENVIRONMENT - Bambang Rusdiarso (Indonesian Journal of Chemistry, 2007)
Synergistic extraction of cobalt(II) with mixture of acyl-pyrazolon (HL) and crown-ether (E) in the Sr(NO3)2 environment has been studied. In this research, HPMBP (phenyl-1-methyl-3-benzoil-4-pyrazolon-5) was used, with three different kinds of  crown-ether, i.e. (benzo-15-crown-5), DB18C6 (dibenzo-18-crown-6) and DB24C8 (dibenzo-24-crown-8), in chloroform. In the bulk environment  of stronsium,  a cobalt coextraction and stronsium occured with species ESrNO3+,Co(PMBP)3-, and E = B15C5,    while Co(PMBP)2E and ESr,Co(PMBP3)2, with E = DB18C6. There was no  coextraction when using crown-ether DB24C8, with the extracted species Co(PMBP)2E. Values of extraction constant presented in log Kex were -6.08 (B15C5), - 4.51,  -12.55 (DB18C6), and - 4.57 (DB24C8), respectively.